The Influence Of The Direct Instruction Learning Model On Learning Outcomes For Basketball Dribble Skills - Lailatul Muflihah; Muchamad Arif Al Ardha; Dwi Lorry Juniarisca; Moh. Fathur Rohman; Sauqi Sawa Bikalawan (International Journal of Educational Technology and Society, 2024)
Learning models have a role in facilitating the process of transferring knowledge carried out by teachers to students. This study applies the direct instruction learning model with the aim of improving dribble skills in basketball learning. This research uses a quantitative approach with a pseudo-experimental method. The sampling technique used was cluster random sampling involving 115 students at junior high school level 1. The results showed that the direct instruction learning model was effectively applied to basketball dribble learning. The increase in the experimental group occurred by 48.90% for the skill variable, and 25.30% for the assessment variable. These results indicate that the direct instruction learning model is better than the conventional learning model. On the other hand, the direct instruction learning model has the possibility of ineffectiveness if applied to other learning and other levels of education.